Evaluating the rate of rock art deterioration in the uKhahlamba-Drakensberg Park, KwaZulu-Natal - Meiklejohn, K.I. (Ian) (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2010.